CONTRIBUIÇÕES DO ESTÁGIO NA CRECHE PARA A CONSTRUÇÃO DA IDENTIDADE PROFISSIONAL DE FUTUROS PROFESSORES - Klinger Teodoro Ciríaco; Janaína Ojeda Rodrigues (Universidade do Oeste Paulista, 2015)
This paper focus basically on a qualitative study of descriptive-analytical nature that was based on the investigation of how much the internship contributes for the initial training and professional identity of Pedagogy students at the Federal University of Mato Grosso do Sul/UFMS/Campus de Naviraí. Thus, through the analysis of interviews with three future female teachers means we sought to understand the process of building their identities in relation to being a teacher in Child Education (day-care center). Two semi-structured interview scripts were utilized: one before starting the internship activities and the other upon completion of discipline. The data analysis showed us that the Pedagogy students had positive expectancies in regard to the experience with babies; however, the fear of the experience is quite remarkable when they think about the pedagogical practice that they will perform as real teachers. Finally, it was evident that the Pedagogy students empathize with child education and its practice, being able to build their own professional identity around it.